Indefinite Integral-F
Indefinite Integral-F
Indefinite Integral-F
INDEFINITE INTEGRAL
In many practical problems, the derivative of a function is given and we are required to find the
function which has the given derivative. The process of finding this function is called integration.
Constant of Integration:
As the differential coefficient of a constant is zero, we have
d d
dx
F x f x dx F x c f x .
Basic formulae:
Antiderivatives or integrals of some of the widely used functions (integrands) are given below:
d xn1 xn1
xn dx
n
x c , n – 1
dx n 1 n 1
d 1 1
dx
(ln | x | )
x
x
dx ln | x | c
d x
dx
(e ) e x
e x dx e x c
d x ax
dx
(a ) (a x ln a) ax dx
ln a
c (a > 0)
d
dx
(sin x) cos x cos x dx sin x c
d
dx
( cos x) sin x sin x dx cos x c
d
sec
2
( tan x) sec 2 x x dx tan x c
dx
d
dx
( cos ec x) ( cot x cos ec x) cos ecx cot x dx cos ecx c
d
dx
( sec x) sec x tan x sec x tan x dx sec x c
d
cos ec
2
(cot x) cos ec 2 x x dx cot x c
dx
d 1 x 1 1 x
dx
sin
a
a2 x 2
a2 x 2
dx sin1 c
a
x
or cos1 c1
a
d x a dx 1 x
dx
tan1 2
a x a2
x 2 a2 a
tan1 c
a
d 1 1
dx
(sec 1 x)
| x | x2 1
x x 12
dx sec 1(x) c
d 1 dx
dx
(cos ec 1x)
| x | x2 1
| x | 2
x 1
cos ec 1x c
cos x
cot x dx sin x dx ln | sin x | c
sin x
tan x dx cos x dx ln | cos x | c ln | sec x | c
Standard Formulae:
dx
x a2 2
ln x x2 a2 c
dx
x a2 2
ln x x2 a2 c
dx 1 xa
x 2
a 2
ln
2a x a
c
dx 1 xa
a 2
x 2
2a
log
xa
c
x a2
x 2 a2 dx
2
x 2 a2
2
ln x x 2 a2 c
x a2
x 2 a2 dx
2
x 2 a2
2
ln x x 2 a 2 c
x 2 a2 x
a2 x2 dx =
2
a x2
2
sin-1
a
c
d d
Proof: We know that ( p (x)) = (p (x)).
dx dx
d
Let f (x) =
dx
(p (x)) p (x) = f(x) dx
2
d
f(x) dx p(x) dx ( p(x)) dx
d
= dx (p(x)) dx f(x) dx
ii) f(x) g(x) dx f(x) dx f(x) dx .
Proof: From the property of differentiation, we have
d d d
p(x) g(x) (p(x)) (g(x))
dx dx dx
d d
If (p(x)) = f (x) and (q (x)) = g (x), then
dx dx
where f1, f2, …, fn are integrable function and 1, 2, …, n are arbitrary constants.
d d
iii) dg f g(x) dx g(x) dx f g(x) .
d d d
Proof: We know that f(g(x)) f g(x) g(x) (Chain rule)
dx dg dx
d d d
dg f g(x) dx g(x) dx dx f g(x) dx = f (g (x)).
1
iv) If f(u)du = F(u) + c, then f(ax + b) dx = F ax b c, a 0.
a
Proof: Write u = ax + b so that du = a dx. Hence
1
f(u)du a f(ax b)dx F(ax b) c 1
f(ax b)dx
a
F(ax b) c .
1 cos 4x
Illustration 1. Evaluate I = cot x tan x dx .
2 cos2 2x 1
Solution: I= cos 2
x sin x 2
. sin x.cos x dx 2 cos 2x 2 sin 2x dx
1 1
=
2sin 4x dx cos 4x c .
8
3
dx
Illustration 2. Evaluate I sin 2
x.cos 2 x
.
sec
2
Hence I = x cos ec 2 x dx = tanx – cotx + c.
dx
Illustration 3. Evaluate cos ecx cot x .
dx
Solution: Let I = cos ecx cot x
cos ecx cot x dx
= cos ec 2 x cot 2 x
cos ecx cot x dx
x
= log tan + log |sinx| + c
2
= log (1 cosx) + c1.
1/2 3/2
Illustration 4. Evaluate 3x (1 + x ) dx.
Solution: When solving such problems it is expedient to use the following trigonometric
identities:
sin(mx) cos(nx) = (1/2) [sin(m – n)x + sin(m + n)x],
sin(mx) sin(nx) = (1/2) [cos(m – n)x – cos(m + n)x],
cos(mx) cos(nx) = (1/2) [cos(m – n)x + cos(m + n)x].
Here cos4x cos7x = (1/2) [cos(3x) + cos 11x]
1
I=
2
cos 3x cos11x dx
1 sin 3x sin11x
c.
2 3 11
dx sin x
Illustration 6. Evaluate (i) 1 sin x , (ii) 1 sin x dx .
dx 1 sin x 1 sin x
Solution: (i) 1 sin x 1 sin x dx cos x dx
2 2
4
sin x sin x 1 1
(ii) Here 1 sin xdx 1 sin x
dx
1
= 1 1 sin x dx
= x (tan x sec x) + c.
Exercise 1.
Integrate the following functions
4 5 sin x cos 2 x cos 2
i) ii)
cos 2 x cos x cos
1 2
iii) x iv) sin x
x
2
x 1
v) 2x 3 cos x + e vi) x
x
Methods of Integration
If the integrand is not a derivative of a known function, then the corresponding integrals cannot be
found directly. In order to find the integrals of complex problems, generally four methods are used
so that the integral is reduced to the standard form.
Integration by substitution or by change of the independent variable.
Integration by parts.
Integration by using trigonometric identities.
Integration by partial fractions.
Integration By Substitution
Direct Substitutions:
If the integral is of the form f(g(x)) g(x) dx, then put g(x) = t, provided f(t) dt exists.
d g(x) dt
g (x) = t
dx
dx
so that the integral f g(x) g(x) dx
dt
become f(t)
dx
dx f(t) dt .
The problem of integrating with respect to x is transformed to integrating f (t) with respect to t and
1 ln x 2
Illustration 7. Evaluate x
dx .
1
Solution: Let 1 + ln x = t so that dx = dt
x
1 ln x 2 1 3 1 ln x 3
I= x
dx = t 2 dt =
3
t +c=
3
c.
5
sin ln x
Illustration 8. Evaluate x
dx .
1
Solution: Let lnx = t. Then dt = dx.
x
sin ln x
Hence I =
x
dx = sint dt = – cost + c = – cos(lnx) + c.
x 2
1 dx
Illustration 9. Evaluate .
x 4 2
3 x 1 tan 1 1
x
x
Solution: The given integral can be written as
1
1 2 dx
x
I=
1
2 1 1
.
x 1 tan x
x x
1 1
Let x t . Differentiating we get 1 2 dx = dt.
x x
dt
Hence I =
t 1 tan1 t
2
.
-1
Now make one more substitution tan t = u. Then
dt du
2
t 1
du and I=
u
ln | u | c
Returning to t, and then to x, we have
1
I ln tan1 t c ln tan1 x c .
x
1
Solution: (i) Let log x = t dx = dt.
x
Substituting in the given integral, we have
dx dt
x(log x)m
m t m dt
t
t m 1 1
= c = (log x)1m c .
m 1 1 m
dx dt
For m = 1,
x log x
t
log | t | c = log |log x| + c
dx
(ii) Let I = xa xb
1 x a x b
= dx
x a x b x a x b
6
xa xb 1
= (a b)
=
(a b)
x a x b dx
1 2 2
= (x a)3 / 2 (x b)3 / 2 c
a b 3 3
2 (x a)3 / 2 (x b)3 / 2 c .
=
3(a b)
Exercise 2.
Integrate the following:
cos x sin x 1
i) , ii) ,
cos x sin x sin 1
x. 1 x 2
x 4 x 6
iii) x loge(ex), iv) 2 ,
x 3 x 100
cos x sec 2 log( x )
v) , vi) .
x x
Standard Substitutions:
2 2
For terms of the form x + a or x 2 a2 , put x = a tan or a cot.
2 2
For terms of the form x – a or x 2 a2 , put x = a sec or a cosec.
2 2
For terms of the form a – x or a2 x 2 , put x = a sin or a cos.
If both a x , a x are present, then put x = a cos.
For the type x a b x , put x = a cos2 + b sin2.
For the type ( x2 a2 x)n or (x x 2 a2 )n , put the expression within the
brackets = t.
1
1 1 1
1 1 x b n 1
For the type x a n x b n or (n N, n > 1),
x a x a 2
xb
put t.
xa
1
For , n1, n2 N (and > 1), again put (x + a) = t(x + b).
x a n x b n
1 2
dx
Illustration 11. Evaluate x 1 6/5
x 3 4 / 5
.
dx dx
Solution: I= x 1 6/5
x 3 4/5
= x 3
4/5
.
x 1 2
x 1
x 3 4
Put = t dt = dx.
x 1 x 12
7
1/ 5
1 dt 5 5x 3
Hence I =
4 t 4/ 5
t1/ 5 c
4 4 x 1
c.
dx
Illustration 12. Evaluate
( x a) (b x )
.
2 2 2
Solution: Writing x = acos + bsin = a + (b a) sin , the given integral becomes
2(b a) sin cos d
I
1/ 2
(a cos2 b sin2 a) (a cos2 b sin2 b
2 b a sin cos d ba
= b a sin cos
=
ba 2 d
x a
= 2 + c = 2 sin1 c.
b a
Indirect Substitutions:
If the integrand is of the form f(x).g(x), where g(x) is a function of the integral of f(x), then put
integral of f(x) = t.
x
Illustration 13. Evaluate a x3
3
dx .
x3 / 2
Solution: Integral of the numerator = .
3/2
3/2
Put x = t.
3
2 dt 2 t 2 x 2
We get, I =
3 a3 t 2
= sin-1
3 a3/2
c sin-1 c .
3 a
sin x cos x
Illustration 14. Evaluate 9 16 sin 2x dx .
sin x cos x
Solution: I= 25 16 sin x cos x 2
dx
1 5 4 sin x cos x
ln c.
40 5 4 sin x cos x
Derived Substitutions:
Some times it is useful to write the integral as a sum of two related integrals, which can be
evaluated by making suitable substitutions.
8
Examples of such integrals are:
A. Algebraic Twins
2x 2 x2 1 x2 1
x 4
1
dx x 4
1
dx x 4
1
dx
2 x2 1 x2 1
x 4
1
dx x4 1
dx x4 1
dx
2x2 2
x 4
1 kx 2
dx, x 4
1 kx 2
dx
B. Trigonometric Twins
1
tan x dx, cot x dx , sin 4
x cos4 x
dx ,
1 sin x cos x
sin 6
x cos x 6
dx , a b sin x cos x dx .
Method of evaluating these integrals are illustrated by mean of the following examples:
x2 1
Illustration 15. Evaluate x 4
x2 1
dx .
1
2 1 2
x 1 x
Solution: Let I = 4 2
x x 1
dx =
2 1
dx .
x 1 2
x
1 1
Put x – = t 1 2 dx dt
x x
dt x2 1
1 t t + c = tan1
–1
I= = tan c.
2 x
1
Illustration 16: Evaluate x 4
1 5 x2
dx .
1 2
Solution: Let I =
2 x 4
1 5x 2
dx
1 1 x2 1 x2 1
=
2 x 4
1 5x 2
dx
2 x 4
1 5x 2
dx
1
1 1/ x 2 1 1 1/ x 2
=
2 x 1/ x
2 2
5
dx
2 x 1/ x 5dx = (I
2 2
1 – I2)/2 (say).
1 1
For I1, we write x – = t (1 + 2 )dx = dt
x x
dt 1 t 1 x 1/ x
I1 = 2
t 7
7
tan1
7
=
7
tan1
7
.
9
1
For I2, we write x + =t
x
1
(1 – )dx = dt
x2
dt 1 t 1 x 1/ x
I2 = t 2
3
3
tan 1
3
=
3
tan1
3
.
2 2 2tdt
Solution: Put tanx = t sec x dx = 2t dt dx =
1 t4
2tdt
I= tan x dx = t 1 t4
2t 2 dt t2 1 t2 1
= 1 t 4
1
= t
t4 14
dt . dt
This can be solved by the method used in Illustration -16.
4
Illustration 19. Evaluate sin 4
x cos 4 x
dx .
1 sin2 x cos2 x
Solution: Let I = 4 sin 4
x cos 4 x
dx = 4 sin x cos x dx
4 4
=4
tan 2
x 1 cos2 x
dx = 4
tan x 1 sec x dx .
2 2
tan 4
x 1 cos 4
x tan x 1 4
2
Now, put tanx = t sec x dx = dt
1 t2 1/ t 2 1
I=4
1 t4
dt = 4
t 2 1/ t 2
dt .
1 1
Now, put t = z 1 2 dt dz
t t
dz 1 z 1 t 1/ t
I= z 2
2 2
= tan1
2
+c =
2
tan1
2
+c
1 1 tan x 1/ tan x
= tan c.
2 2
2 cos xdx
Illustration 19. Evaluate 3 4 sin 2x .
2 cos xdx cos x sin x cos x sin x
Solution: Here 3 4 sin 2x 3 4 sin 2x dx 3 4 sin 2x dx
10
cos x sin x dx cos x sin x dx
= 3 4 1 sin x cos x 2 3 4 sin x cos x 2 1 .
In the first integral put sinx – cosx = t, in the second integral put sinx + cosx = y,
and proceed.
Similarly, we can solve integrals of the type:
1 1
a sin x bsecx
dx,
p cos x q cos ecx
dx .
dx
Illustration 20: Evaluate 2 sin x sec x .
dx cos xdx 1 cos x sin x cos x sin x
Solution: Let I = 2 sin x sec x sin 2x 1 2 sin 2x 1
dx
1 2 sin x cos x 1
= ln c.
4 2 2 sin x cos x 2 sin x cos x
Exercise 3.
Integrate the following functions:
1 x2 1
i) cot x ii) iii)
x 3x2 9 x
4 2
2
1
sin 2 x x 1
iv) v) vi)
p cos 2 x q sin2 x x4 1 cot x
11
dt
cot x dx t = log |t| + c = log |sin x| + c
(iii) sec x dx = log |secx + tanx| + c.
sec x(sec x tan x)
Proof: Here sec x dx sec x tan x
dx
1
= log c
cos ecx cot x
(cos ecx cot x)
= log c
cos ec 2 x cot 2 x
= log |cosec x cot x| + c.
sin 2x sin 2x
Solution: (i) We have sin 4x dx 2 sin 2x cos 2x dx
1 1
=
2
sec 2x dx
4
sec t dt
where 2x = t
1 1
= log |sec t + tan t| + c = log |sec 2x + tan 2x| + c.
4 4
1 sin x 1 2 sin x / 2 cos x / 2
(ii) Here
1 cos x
dx
2 sin2 x / 2
dx
1 x x 1 cot x / 2 x
=
2
cos ec 2 dx cot dx =
2 2 2 1/ 2
2 log sin c
2
x x
= cot 2 log sin c .
2 2
sin sin
7 6
(iii) We write x dx x sin x dx
(1 cos
2
= x)3 sin x dx .
12
Let cos x = t sin x dx = dt.
sin
7
Hence x dx (1 t 2 )3 dt
3 1
= (1 3t 2 3t 4 t 6 ) dt = t t 3 t 5 t7 c
5 7
3 1
= cos x cos3 x cos5 x cos7 x c .
5 7
a sec 2 d 1 1 x
I= a sec 2 2
a
a
d c tan1 c .
a a
dx dx 1 1 1
I= 2
a x 2
(a x)(a x) 2a a x a x
dx
1
= log | a x | log | a x | c
2a
1 ax
= log c.
2a ax
Alternatively, we may write x = a sin and get
1 1 1 1 sin 2
I=
a
sec d log | sec tan | c =
a 2a
log
cos2
c
1 1 sin 1 ax
= log c log c.
2a 1 sin 2a ax
dx
I= x a2
2
; we write x = a tan and get
x x 2 a2
= log c.
a
a2 a2 1
I = a2 cos2 d
2 (1 cos 2) d
2 2 sin 2 c
13
a2 a2 x x a2 x 2
= sin cos c sin1 c
2 2
a a2
a2 x x a2 x 2
= sin1 c.
2 a 2
dx
I= | x | x 2 a2
; we write x = a sec , dx = a sec tan d and get
a sec tan d
I= | a sec | | a tan | .
x
Since = sec1 and its range 0, , ,
a 2 2
a sec a tan is positive. Hence
1 1 x
I=
a
d sec 1 + c.
a a
Remarks: If f (x) is a differentiable function of x, then
f (x)
(i)
2
1 f (x)
dx tan1 f(x) c
f (x)
(ii) 2
1 f (x)
dx sin1 f(x) c
f (x)
(iii) f(x) dx log f(x) c
by writing f (x) = t.
1 x2 a 1 x2 a
=
2a x 4
a2
dx
2a x 4
a2
dx
1 1 a / x2 1 1 a / x2
=
2a x 2
a /x 2 2
dx
2a x 2
a2 / x 2
dx
1 1 a / x2 1 1 a / x2
=
2a a
2
a
dx
2a 2
dx .
x x 2a x x 2a
a a
Writing x t and x = z, we get
x x
1 dt 1 dz
I=
2a t 2 2a 2a z2 2a
1 1 t 1 z 2a
= tan1 log c
2a 2a 2a 2a 2 2a z 2a
14